Analisis Pemanfaatan Platform TikTok sebagai Media Aktualisasi Diri Peserta Didik - Sofa, Nurul Aeni; Annaafi’atsaani, Irbasabila; Ihsanuddin, Ahmad Noor; Anbiya, Bakti Fatwa (PT The Collaboration UVW, 2023)
Times are getting more advanced as well as more and more social media available as information and communication services. The social media application TikTok is in great demand by all groups, especially teenagers or students. The social media application TikTok can be used in various fields. In the TikTok application, everything has been presented in audio-visual form. With TikTok, students can carry out learning. Not only for learning, but TikTok is a tool or means of self-actualization where students can express and develop their potential in cyberspace to achieve their desires. The purpose of this writing is to find out how students use and utilize social media TikTok as a means of self-actualization. The method used in this research is a case study. Where data collection is carried out by observing an account on the TikTok application. Namely the tiktok account from @Zulkar_na which has 168.7 thousand followers, and 8.5 million likes, and the video with the most viewers, namely 17.6 million viewers. From the results of this study, it can be obtained that students use TikTok social media to express themselves in cyberspace as well as to obtain and share various information because TikTok social media is a comfort zone for all people to make it easier to get everything they want.